Mediatization of Islam in the Digital Era: Opportunity or Threat? - Sukarman ,; Fatah Syukur,; Raharjo . (TAWASUT, 2021)
Abstract. The religious activities of Muslims have experienced a shift in the digital era 4.0. The tremendous development of information technology has changed the religious pattern of Muslims around the world. This paper aims to answer how the form of a religious shift in the Muslim community, to what extent the development of information technology has implications for the religious pattern of Muslims. The approach used in this qualitative descriptive study is a phenomenological approach. The research data was extracted through documentation from several kinds of literature, both books, and scientific journal articles. The data is then analyzed to obtain answers to the research questions. The result of this research is that ibadah activities and muamalah activities have been affected by advances in information technology so that they experience a shift in religious patterns from manual to online-based. The conclusion of this paper is that technological progress has not only contributed greatly to the religious pattern of Muslims but has also become a threat to Muslims. Keywords: Islam, media, digital era.